PENANGANAN MASALAH TRAUMA - Sri Utami (Sosio Informa, 2005)
(Coping of Trauma Problem) - Trauma in an unpleasant empirical experience which is happened in someone life. Trauma is caused by unpleasant experience which always he/she remember in his/her mind so that he/she afraid that the bad experience will be happened again in his/her life. That feeling is comprehended by someone and that feeling can be distinguished by seeing how heavy or light that traumatic experience. The neediness of client to recover from trauma problem is having back the client's self esteem and dignity as individual human rights. Solution program to stop this problem are family therapy program and caunseling program. a social worker intervention is helping to stop problem by doing mediation service approach and individual counseling service approach.